Evaluation of Quality of Life After Use the Virtual Reality in Patients with Neurodegenerative Disease - Malisky, Jéssica Spricigo; Cavalcante-Leão, Bianca Lopes; Severiano, Maria Izabel; dos Santos, Geslaine Janaina Bueno; Teive, Hélio Augusto Guizoni; José, Maria Renata; de Araújo, Cristiano Miranda; Zeigelboim, Bianca Simone (International Archives of Otorhinolaryngology, 2024)
Introduction Spinocerebellar ataxias (SCAs) are a heterogeneous group of neurodegenerative diseases.Objective To evaluate the living standard of patients with SCA, by applying the Vestibular Disorders Activities of Daily Living Scale (VADL) and Activitiesspecific Balance Confidence Scale (ABC) questionnaires.Methods An uncontrolled clinical trial study was conducted with 28 patients who underwent anamnesis, ENT evaluation, and vestibular assessment and the application of questionnaires VADL and ABC before and after rehabilitation with virtual reality.Results The vestibular exam was altered in 64.3% of the cases. The result between the correlation of the VADL and ABC questionnaires showed significant results in all cases (p < 0.005). The correlation between the ages and disease length with the VADL and ABC questionnaires was significant in the T3 assessment (p = 0.015). The correlation between the disease length and the VADL questionnaire was significant in all cases (p < 0.005). The comparison of the vestibular rehabilitation result (T1 to T2) showed a significant difference for all the applied games, except for the ski slalom. The comparison of the vestibular rehabilitation result (T1 to T3) showed significant difference for all the applied games (p < 0.005) (1st assessment before the start of rehabilitation designated T1, after 10 rehabilitation sessions, considered T2 and, at the end of 20 rehabilitation sessions, called T3).Conclusion We can point out a direct improvement in the living standard, reflected by the reduction of falls, better balance, and march, contributing to a higher self-confidence in patients in daily activities.
Keywords: Ataxia; quality of life; rehabilitation; neurodegenerative diseases; postural balance